Practical application of health literacy tests at the primary level of health care - Joković Sandra; Kekuš Divna; Mijović Biljana (Association of Nurses Technicians and Midwives, 2019)
According to the World Health Organization, quality communication is one of the five skills that individuals need for a healthy and happy life, and the knowledge and skills of quality communication are a prerequisite for quality action for many professions. In order for healthcare professionals to tailor health communication to each patient individually and to provide high quality healthcare, it is essential that they have an insight into the health literacy status of their users. Given the large percentage of the illiterate population around the world, it is necessary to conduct health literacy research in some of our adapted measuring instruments in our country as well.